A comparison of cross sections for Selenium -73 radioisotopes produced by accelerators and reactors - Abd al-Rida, Muhammad A.; Naji, Nawal F.; Amir, Ikhlas J. (Al-Kindy College medical journal, 2022)
Background: Selenium-73 with half- life of 7.15 hour emits β + in nature and has six stable isotopes which are ( 74Se,76Se,77Se,78Se,80Se and 82Se ). Selenium-73 has many applications in technology and radioselenium compounds of metallic have found various applications in medicine. Objective: To make a comparison between different reactions that produced cross sections of Se-73 radioisotopes. Subjects and methods: The feasibility of the production of Selenium -73 via various nuclear reactions was investigated. Excitation functions of 73Se production by the reactions of 75As (p,3n), 169Tm( d,x), 74 Se, natSe, natBr (p,x) , 75As (d,4n), natGe (3He,x), 70Ge (α, n), and 72Ge (α, 3n) and neutron capture were calculated using the available data in the international libraries in accordance with SRIM code . Theoretical calculations of the thick target integral yields were deduced using the calculated cross sections by using Matlab program Results: When proton induced reaction on 75As, 74Se, natSe and natBr to obtain 73Se, the reaction 75As(p,3n) with range of energy (22.5 to 45.5 MeV) and the maximum cross section is 315 mb at 36.5 MeV gives maximum yield (2*106 GBq/C).while for the reaction 75As (d,4n) 73Se with range of energy (25 to 56 MeV) , and maximum cross sections is 30 mb at 43MeV gives (0.085*106 GBq/C). The three reactions natGe (3He,x) , 70Ge (α,n) and 72Ge (α,3n) show that the best reaction to obtain 73Se is 72Ge (α,3n) within the range of energy (27 to 46 MeV) and maximum cross sections 494 mb at 42MeV give the maximum yield (0.03*106 GBq/C). Conclusion: the use of proton as projectile is best compared with other particles in order to get maximum isotopes production yield of 73Se